Suhu Udara Dengan Kasus Konfirmasi COVID-19 di Kota Surabaya - Ratna Maya Paramita; Haryoto Kusnoputranto; Budi Hartono (Jurnal Kesehatan Lingkungan, 2021)
WHO declares COVID-19 as a global pandemic on March 11th, 2020. Indonesia has confirmed the first case for COVID-19 is on March 2nd, 2020. That case happens in Depok City. Then Jawa Timur Province already confirms for the COVID-19 case is on March 17th, 2020. In particular, there are six persons that have been confirmed to be Surabaya citizens. Infection of COVID-19 is caused by SARS-Cov-2 which has an ability for human-to-human transmission. The aim of this study is to capture the relation between air temperature with confirmed cases of COVID-19 in Surabaya City, 2020. The data provider for this study is the Board of Meteorology, Climatology, and Geophysics (BMKG) Perak I Surabaya, and the Surabaya Health Office. The research design of this study is an ecological study-time series analysis from March to November 2020. This study found that negative correlation between air temperature with confirmed cases of COVID-19. The strength of correlation was 0,305. The direction of that correlation is negative, which means the increasing air temperature so the case confirmation of COVID-19 is decreasing. Surabaya Health Office can do a massive briefing to Surabaya citizens to stand under the sun rays in the morning.